Accountability Criminal Fines in the Perspective of Indonesian Criminal Law - Cahyaningsih, Sinar Indah; Ma'ruf , Tri Abriana; Arif, Mohammad (HORIZON PUBLIC LEGAL STUDIES, 2025)
This research aims to determine and analyze Criminal Liability for Fines in the perspective of Criminal Law. This research was conducted with a normative-empirical type that uses primary legal materials or is a study by going directly to the location, namely at the Makassar Police and journals or references related to the research. The results of this study indicate that (1) Criminal liability for fines in the perspective of Indonesian criminal law generally follows what actions are carried out by the perpetrators of the crime and how much loss from the proceeds of their crime. One example of a drug dealer case where the amount of the fine is up to billions because drug distribution is very detrimental to drug abusers. This means that it is subjective in terms of the actions of the perpetrators of the crime. (2) The achievement of the objectives of criminal punishment against criminal fines has probably not been achieved due to several factors, namely the absence of real evidence of a deterrent effect obtained by the perpetrators of the crime, the amount of the fine given to the perpetrators of the crime is still subjective, and the fine is only an additional punishment, not the main punishment. The recommendation of this research is that law enforcers in criminal liability for a criminal act should be given a heavy fine, even if possible exceeding the loss caused to the victim so that there is a deterrent effect not to commit a criminal act and the fine should be the main punishment so that it can increase the deterrent effect on the perpetrator of the crime, because the purpose of the main punishment, for example imprisonment, is so that the perpetrator of the crime will no longer commit acts that harm people. Therefore, the fine should be made the main punishment and the amount of the fine must exceed the loss caused by the perpetrator